Prevalence and Risk Indicators of Depressed Mood in On-Reserve First Nations Youth - Lemstra, Mark E. (Can J Public Health, 2011)
OBJECTIVES: The first objective was to determine the prevalence of depressive mood in First Nations youth in school grades 5 through 8 in seven onreserve communities. The second objective was to determine the unadjusted and adjusted risk indicators associated with depressed mood in these youth. METHODS: Students in grades 5 through 8 in the seven reserve communities of the Saskatoon Tribal Council were asked to complete a paper and pencil, comprehensive youth health survey in May 2010. An eight-stage consent protocol was followed prior to participation. RESULTS: Out of 271 students eligible to participate, 204 youth completed the survey for a response rate of 75.3%. Using the Center for Epidemiological Studies of Depression scale, 25% of the youth had moderate depressive symptoms. After cross-tabulation, 1 socioeconomic variable, 10 social variables, 3 social support variables, 1 self-esteem variable, 5 parental relationship variables and 3 bullying variables were associated with depressed mood. Logistic regression was used to determine four independent risk indicators associated with having depressed mood in First Nations youth, including: 1) not having worked through things that happened during childhood, 2) not having someone who shows love and affection, 3) having a lot of arguments with parents and 4) being physically bullied at least once per week. CONCLUSIONS: Our study found high rates of depressed mood in on-reserve First Nations youth. These youth are now at increased risk for problems later in life unless successful interventions can be implemented.